Pesquisa da adição de soro de queijo ao leite pasteurizado comercializado em Minas Gerais: determinação de CMP por cromatografia líquida de alta eficiência (CLA) e comparação dos métodos imunoquímicos (Stick cGMP e BRW Elisa) - Paula Rita Lobato (2014)
Cheese whey is a nutritious by-product from dairy industries. However, due to low commercial value and difficulty of detection, it is frequently used to adulterate milk. In Brazil, the caseinomacropeptide (CMP) determination by gel filtration high performance liquid chromatography (HPLC) is the official method to investigate cheese whey addition to the milk. CMP concentration is supposed to be equal or less to 30 mg/L. If CMP content ranges from 30 to 75 mg/L, the milk should be used only for specific dairy products, and if the level is higher than 75 mg/L, the milk shall be used strictly for animal feeding. The objective of this study was to evaluate the level of CMP by HPLC to detect fraudulent addition of cheese whey to the pasteurized milk, in the Minas Gerais state. Fifty six samples of milk were collected from retailers located in six regions of Minas Gerais State, Brazil, and kept under refrigeration until analysis. Only 68 percent of the samples were in compliance with the legal requirements of CMP up to 30 mg/L. Two percent of the samples presented CMP levels from 30 to 75 mg/L and 30 percent of the samples showed levels of CMP higher than 75 mg/L. Immunochemical methods (Stick cGMP and BRW Elisa) were compared to HPLC, without significant difference (p>0.05) among the methods. Milk quality inspection through CMP monitoring by HPLC or immunochemical methods is an important tool to minimize or prevent milk adulteration with cheese whey.